Analysis of Methods and Strategies for Integrating Artificial Intelligence into Computer Technology - Zhou, Xiaoliang; Sun, Xiaofei (Journal of Theory and Practice of Management Science, 2025)
Computer technology plays an important role in the development of society. With the rapid development of society, traditional computer technology can no longer meet the actual needs of current users. In order to change the current situation, artificial intelligence and computer technology should be integrated to achieve technological innovation, enhance the application ability of computer technology, and expand the application scope of information technology.This article analyzes the integration of artificial intelligence and computer technology, analyzes the specific applications of artificial intelligence, and forms specific application strategies, in order to provide reference and guidance for related research.